Lactose intolerance in allergic enterocolitis in infants - O.G. Shadrin; H.A. Haiduchyk (Zaslavsky O.Yu., 2019)
Background. Food allergy in the infancy is manifested clinically in damage to the skin and gastrointestinal tract. Allergic inflammation of the intestinal mucosa is accompanied by damage to the structure of enterocytes, which can lead to a significant reduction in the lactase enzyme on their apical surface. Materials and methods. Sixty-two children aged 2 months to 1 year with allergic enterocolitis were examined. To diagnose lactase deficiency, a hydrogen breath test with food lactose load was performed using portable monitor for determining hydrogen (H2) concentration in the exhaled air - Gastro+ Gastrolyzer manufactured by Bedfont Scientific Ltd. (UK). Results. Comprehensive assessment of the results of a hydrogen breath test with food lactose load revealed the presence of lactase deficiency and lactose-dependent small intestinal bacterial overgrowth in children with allergic enterocolitis: in protein-induced enterocolitis syndrome - in 70.3 and 14.8 % of cases, respectively, in protein-induced enteropathy - in 100.0 and 41.6 %, in protein-induced proctocolitis - in 36.0 and 32.0 % of infants, respectively. Conclusions. According to the results of a hydrogen breath test with food lactose load, 40 (62.5 %) infants with allergic enterocolitis have been diagnosed with lactose intolerance and 17 (26.6 %) - with lactose-dependent small intestinal bacterial overgrowth that are secondary and need correction in the acute period of treatment for the underlying disease.